1999
DOI: 10.1097/00005768-199908000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Physical performance in persons with spinal cord injuries after discharge from rehabilitation

Abstract: It is concluded that physical capacity and performance of ADL improved or remained constant during the first year after rehabilitation and that sport participation is associated with improvements in physical capacity. Results of this study underline the importance of being physically active during the period after rehabilitation of persons with spinal cord injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 11 publications
2
29
0
Order By: Relevance
“…First, we tested able-bodied participants, so that we were able to avoid the influence on LRC of potential respiratory and/or motor problems that are associated with spinal cord injuries or that may have resulted from secondary medical complications associated with wheelchair use (Glaser, Sawka, Young, & Suryaprasad, 1980;Janssen, van Oers, Hollander, Veeger, & van der Woude, 1993). Nonwheelchair-dependent populations also tend to be more homogeneous and can be challenged to a greater degree during wheelchair exercises (van der Woude, van Croonenborg, Wolff, Dallmeijer, & Hollander, 1999). Challenge may be operationalized as the participant's energy expenditure or power output, which is the product of velocity and any resistance (e.g., air and friction) that the participant encounters during the task.…”
Section: Goals Of the Present Studymentioning
confidence: 99%
“…First, we tested able-bodied participants, so that we were able to avoid the influence on LRC of potential respiratory and/or motor problems that are associated with spinal cord injuries or that may have resulted from secondary medical complications associated with wheelchair use (Glaser, Sawka, Young, & Suryaprasad, 1980;Janssen, van Oers, Hollander, Veeger, & van der Woude, 1993). Nonwheelchair-dependent populations also tend to be more homogeneous and can be challenged to a greater degree during wheelchair exercises (van der Woude, van Croonenborg, Wolff, Dallmeijer, & Hollander, 1999). Challenge may be operationalized as the participant's energy expenditure or power output, which is the product of velocity and any resistance (e.g., air and friction) that the participant encounters during the task.…”
Section: Goals Of the Present Studymentioning
confidence: 99%
“…Subsequently, an inactive lifestyle may further reduce physical capacity. 2,3 A low level of physical capacity is associated with a decrease in activity, 3,4 functional status 5,6 and participation. 2,7 This may result in the vicious circle of decreased physical capacity leading to decreased activity and participation, which further reduces physical capacity, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Important prerequisites for ADL are upper extremity function 4,5 and physical capacity. 6 Other important factors are age, gender, body mass, 7 physical fitness, 7,8 motivation, psychosocial status, medical complications 8 and sociocultural background. 9 Earlier studies 5,10 have shown that preserved motor level can predict the ability of patients with cervical SCI to become independent in ADL.…”
Section: Introductionmentioning
confidence: 99%